Experimental and numerical dynamic identification of a historic masonry bell tower accounting for different types of interaction. Issue 109 (June 2018) - de Silva, Filomena; Pitilakis, Dimitris; Ceroni, Francesca; Sica, Stefania; Silvestri, Francesco
Abstract: Advances in dynamic numerical analyses and investigation techniques nowadays allow to simulate the seismic behavior of structures through increasingly detailed models, calibrated on in-situ dynamic surveys. The different factors affecting the calibration procedure should, however, be well identified and properly represented in the model. Usually various forms of interaction may influence the building response (i.e. soil-structure, surrounding buildings, etc.) and so their single contribution on the overall response of the coupled system should properly be ascertained. In the paper, the results of numerical analyses and on-site dynamic identification are compared, to quantify the role exerted by the structure, the foundation, the soil and the adjacent buildings on the overall dynamic behavior of the highest tower in Napoli (Italy). The experimental frequencies and the corresponding deformed shapes were reproduced through a simplified model on springs, simulating the soil-foundation impedance. The inferred dynamic behavior of the tower was observed to be significantly influenced by the restraint exerted from adjacent buildings and by the interaction with the soil. The results were corroborated by the more refined predictions provided by a complete 3D Finite Difference model of soil, foundation and structure. In addition, a frequency detected from field records, which has not been identified in previous analyses on fixed base models, was found to be associated to the rocking response of the foundation. Highlights: Equations of the dynamic impedance of flexible foundations are reported; Results of uncoupled and coupled soil-structure analyses are compared to field records; The effect of adjacent buildings and foundation embedment and flexibility is studied; A novel procedure is proposed for the dynamic identification of coupled SFS models; The frequency associated to the foundation rocking is recognized.